Trajectories of Depressive Symptoms, Neurocognitive Function, and Viral Suppression With Antiretroviral Therapy Among Youth With HIV Over 36 months. (1st June 2021) - Kohn, Jordan N.; Loop, Matthew Shane; Kim-Chang, Julie J.; Garvie, Patricia A.; Sleasman, John W.; Fischer, Bernard; Rendina, H. Jonathon; Woods, Steven Paul; Nichols, Sharon L.; Hong, Suzi
Abstract : Background: Depression and neurocognitive impairment are highly prevalent among persons living with HIV and associated with poorer clinical outcomes; however, longitudinal studies of depression–neurocognition relationships in youth living with HIV (YLWH), and the role of antiretroviral therapy (ART), are lacking. This study tested whether (1) depressive symptomatology, across somatic, cognitive, and affective symptom domains, improved with ART and (2) more severe depressive symptoms at baseline were associated with poorer neurocognitive function and poorer HIV suppression. Setting: Data were collected from 181 YLWH (18–24 years) who were treatment-naive, a subset of whom (n = 116) initiated ART. Methods: Participants were categorized into elevated (DS) or nonelevated (non-DS) depressive symptom groups at entry (Beck Depression Inventory-II ≥14) and followed for 36 months. Neurocognition (5-domain battery) and depressive symptoms were repeatedly assessed. Longitudinal models examined depressive symptomatology, neurocognition, and odds of HIV nonsuppression by group. Results: Greater improvements in depressive symptoms were observed in the DS group over 36 months [beta = −0.14, (−0.24 to −0.03)], particularly within cognitive and affective domains. Verbal learning performance increased in the DS group [beta = 0.13, (0.01 to 0.24)], whereas psychomotor function improved somewhat in the non-DS group [beta = −0.10, (−0.22 to 0.00)]. Adjusted for ART adherence, odds of HIV nonsuppression did not significantly differ by group [odds ratio = 0.22, (0.04 to 1.23)]; however, greater somatic symptoms at study entry were associated with an increased risk of nonsuppression over time [odds ratio = 2.33 (1.07 to 5.68)]. Conclusion: Depressive symptoms were associated with differential neurocognitive trajectories, and somatic depressive symptoms at baseline may predict poorer subsequent HIV suppression. Identifying and treating depressive symptoms at ART initiation may benefit neurocognitive and clinical outcomes in YLWH. Abstract : Supplemental Digital Content is Available in the Text.